Increasing the social responsibility of oil and gas companies in the context of the green economy formation: Russian and Western experience - A. Z. Gusov; E. V. Lylova; E. V. Kolganova; M. M. Eyeberdiyeva (Модернизация, инновация, развитие, 2022)
Purpose: the main idea of the article is to prove that the level of corporate social responsibility (hereafter CSR) of large gas and oil companies can be improved. This is a necessary condition for providing sustainable development of these companies because on the one hand the new paradigm of their development considers transition to low-carbon technologies, on the other hand, the main activity of gas and oil companies is associated with natural resources consumption, which inevitably leads to certain negative environmental consequences. At the same time, it is these consequences that trigger the process of establishing a green economy.Methods: the authors conducted a comparative and iterative analysis of the CSR development process of four major Western and four major Russian oil and gas companies.Results: large oil and gas companies around the world are deeply involved into the implementation of various areas of CSR in different directions to ensure long-term sustainable development. Our analysis showed that CSR areas are different and correspond to the basic set of CSR activities. Also, there are more advanced activities, though this applies only to individual companies. Oil companies have demonstrated certain features in their CSR practice, such as the variety of issues being addressed, the wide presence of intersectoral partnerships, and interaction with social entrepreneurs. However, not all companies are equally involved in the implementation of CSR.Conclusions and Relevance: the results of research allow us to determine the main reserves for improving the competitiveness of the analysed companies. The practical application of the results of this study is possible in the field of corporate governance, strategic planning for oil and gas companies. The results of the study are also of interest from the point of view of the development of scientific ideas about modern ways of implementing corporate social responsibility and the specifics of its implementation in the oil and gas industry.